CD4+ T helper 17 cell response of aged mice promotes prostate cancer cell migration and invasion. Issue 10 (1st May 2020) - Liu, Sen; Liu, Fengli; Zhang, Bing; Yan, Peng; Rowan, Brian G.; Abdel‐Mageed, Asim B.; Steele, Chad; Jazwinski, S. Michal; Moroz, Krzysztof; Norton, Elizabeth B.; Wang, Alun; Myers, Leann; et al.
Abstract: Background: Aging is the most important risk factor for prostate cancer (PCa), but how age contributes to PCa is poorly understood. Aging is characterized by low‐grade systemic inflammation (i.e., inflammaging) that is often attributed to the progressive activation of immune cells over time, which may play an important role in prostate carcinogenesis. Th17 response is elevated in aging humans and mice, but it remains unknown whether it is increased in prostate tissue or contributes to prostate carcinogenesis during aging. In this study, we aimed to determine the role of age‐related Th17 response in PCa cell growth, migration, and invasion. Methods: C57BL/6J (B6) mouse was used as an aging animal model and the prostate histopathology during aging was analyzed. Splenic CD4 + T cells were isolated from young (16‐20 weeks old) and aged (96‐104 weeks old) mice, and cultured in the presence of plate‐bound anti‐CD3/anti‐CD28, with or without Th17 differentiation conditions. The cells were collected and used for subsequent flow cytometry or quantitative reverse transcription polymerase chain reaction. The supernatant was collected and used to treat PCa cell lines. The treated PCa cells were analyzed for cell viability, migration, invasion, and nuclear factor kappa B (NF‐κB) signaling. Results: Aged mice had enlarged prostate glands and increased morphological alterations, with not only increased inflammatory cell infiltration but also increased Th17 cytokines in prostate tissue, compared to young mice. Naïve CD4 + T cells from aged mice differentiated increased interleukin (IL)‐17‐expressing cells. CD4 + T cells from aged mice spleen had increased Th17 cells, Th17 cytokines and Th17/Treg ratio compared to young mice. Factors secreted from aged CD4 + T cells, especially from ex vivo differentiated Th17 cells, not only promoted PCa cell viability, migration, and invasion but also activated the NF‐κB signaling in PCa cells compared to young mice. Conclusions: These results indicate that age‐related CD4 + T cells, especially Th17 cells‐secreted factors have the potential to contribute to prostate carcinogenesis. Our work could prompt further research using autochthonous PCa mouse models at different ages to elucidate the functional role of Th17 response in prostate carcinogenesis during aging.